1967
DOI: 10.1113/jphysiol.1967.sp008321
|View full text |Cite
|
Sign up to set email alerts
|

Athletes at altitude

Abstract: SUMMARY1. Six international middle-distance runners were investigated during 4 weeks in England and during a similar period in Mexico City (2270 m (7450 ft.)) 2. In 3-mile (4828 m) time trials at 2270 m the increase in time taken by four subjects compared with sea level was 8-5 % on the 4th day and 5-7 % on the 29th day. There was thus a gain of 2-8 % or 20 sec in time associated with acclimatization.3. In 1-mile (1609 m) time trials the times were increased by 3*6 % in the first week at altitude and by 1F5 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
1

Year Published

1968
1968
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 29 publications
4
22
1
Order By: Relevance
“…The times in the 5000 m and 10,000 m events were respectively 6 1 and 6-5 % slower than sea level world records (Table 3). A similar result was reported by Pugh (1967) on a party of British athletes in Mexico City in 1965. The British athletes ran 5-8 % more slowly in 3-mile trials at altitude than in control races in England, while the reduction of 0o, max in ergometer exercise was 7x9 % in the four best adapters.…”
Section: Discussionsupporting
confidence: 87%
“…The times in the 5000 m and 10,000 m events were respectively 6 1 and 6-5 % slower than sea level world records (Table 3). A similar result was reported by Pugh (1967) on a party of British athletes in Mexico City in 1965. The British athletes ran 5-8 % more slowly in 3-mile trials at altitude than in control races in England, while the reduction of 0o, max in ergometer exercise was 7x9 % in the four best adapters.…”
Section: Discussionsupporting
confidence: 87%
“…Winter sports, as well as disciplines from other sports, regularly hold competitions at altitudes ϳ2,500 m. Even the mild hypoxia associated with such altitudes impairs VO 2 max by reducing CaO 2 (22,43), and this appears to be pronounced in highly trained individuals (30,31). Athletes may attenuate this undesirable effect by means that stimulate erythropoiesis and thus normalize arterial blood O 2 content.…”
Section: Effect Of Lhtl On Vo 2 Max In Hypoxiamentioning
confidence: 99%
“…Some endurance disciplines, such as cross-country skiing, frequently perform competitions at moderate altitudes. However, even the mild hypoxia associated with these altitudes may decrease maximal oxygen uptake (VO 2 max) by reducing arterial O 2 content (CaO 2 ) (22,43), and this mechanism seems to be particularly pronounced in highly trained athletes (30,31). It appears plausible that this detrimental effect of moderate altitude could be counterbalanced by measures that enhance CaO 2 .…”
mentioning
confidence: 99%
“…Although equivocal, human studies have demonstrated that either hypobaric or normobaric hypoxia per se is responsible for increases in blood haemoglobin (Hb) concentration (Berglund 1992), muscle mitochondrial volume, capillary supply (Desplanches et al 1993), aerobic enzyme activities and myoglobin concentration (Terrados et al 1990), 2,3-diphosphoglycerate (Mairbaurl et al 1986), rate of free fatty acid mobilisation (Young et al 1982) or an elevated blood bu ering capacity (Favier et al 1995). Altitude acclimatisation improves physical performance at altitude (Pugh 1967;Maher et al 1974), but the e ects on sea-level performance are less clear. Since the 1950's, 64 out of 91 studies on the e ects of altitude training on sea-level endurance performance have been conducted without a performance-matched control group trained in normoxia, and of the 15 controlled investigations, only 4 have reported performance-enhancing bene®ts .…”
Section: Introductionmentioning
confidence: 97%